Effects of TiO2 and SDC addition on the properties of YSZ electrolyte. (12th November 2019) - Shen, Chin-Tien; Lee, Kan-Rong; Hsieh, Yu-Pin; Lee, Sheng-Wei; Chang, Jeng-Kuei; Jang, Shian-Ching; Tseng, Chung-Jen
Abstract: In this study, we investigate the effects of adding titanium dioxide (TiO2 ) and samarium doped cerium oxide (SDC) on the properties of yttrium-stabilized zirconia (YSZ) electrolyte. The microstructure, mechanical, and electrochemical properties of the electrolyte are investigated. The performance in CO2 electrolysis is measured by supplying carbon dioxide to Ni-YSZ electrode and nitrogen to LSM electrode. Results show that TiO2 and SDC addition can reduce the sintering temperature and increase grain size. The ionic conductivity is 0.123 S cm −1 at 1000 °C. In addition, the thermal expansion coefficient at 1000 °C is 8.25 × 10 −6  K −1 . The current density of the cell is 439 mA cm −2 at 1.3 V and 1000 °C in solid oxide electrolysis cell. Highlights: Effects of SDC and TiO2 doping on YSZ properties are investigated. TiO2 and SDC addition reduces the sintering temperature and increases grain size. TiO2 and SDC addition increases conductivity to 0.123 S cm −1 at 1000 °C. An LSM/3TiYSZ-SDC/Ni-YSZ single cell is successfully assembled. The CO2 electrolysis current density reached 439 mA/cm 2 at 1.3 V.